(3GdYhdeI h GdJQHjI (B/s - (3YGHO, QSej Ydjs ((3YeGf(B: s (3OGQ LQjQ ddfTQ h GdJhRjY(B, s, 2008)
(3jJVef gPG GdcJGH ehVhY GdYhdeI hGdJQHjI MjK bSeg eDdag Edi SJI aUhd HOCge HJegjO Ke GdaUd GdChd GdMedI GdLOjOI ef GdYhdeI ddbVGA Ydi GdGSdGe Ke GJHYg HaUd KGfj COhGJ GdYhdeI hGdaUd GdKGdK YhdeI YbjOI GdQCS eGdjI hJCKjQgG GdJQHhj GdaUd GdQGHY YhdeI GdQCS eGdjI GdZQHjI deaGgje GdJGQjN ,GdaUd GdNGeS YhdeI efGgL GddZI hGdCOH (B...(3QCS eGdjG MSH GdefgL GdZQHj GdaUd GdSGOS gMeI (B((3YhdeI(B)s
(3HjHdjhZQGajG U(B.373s
Keywords: (3GdGbJUGO GdYGdejs; (3GdJQHjI(B--(3adSaIs; (3GdYhdeIs